Terricolous Lichens in India Volume 2: Morphotaxonomic Studies - Rai, Himanshu; Upreti, Dalip K.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
Terricolous lichens, a habitat specialist group of lichens play a vital role in maintenance and ecological stability of soil crusts with reference to their physical stability, hydrology and growth of soil microflora. Terricolous Lichens in India, Volume 2: Morphotaxonomic Studies is the first lichenological study of this functional group. Based upon extensive field collections and the investigation of approximately 4,500 specimens preserved in various national and international herbariums, Terricolous Lichens in India: Volume 2: Morphotaxonomic Studies focuses on the morphotaxonomy of terricolous lichens in India. Divided into two chapters, the first chapter describes the basics of soil lichen curation from Indian habitats, presents the various morpho-anatomical and chemical techniques for taxonomic identification, and introduces the morpho-anatomical features of terricolous lichens. The second chapter focuses on the taxonomy of 312 terricolous lichen species and includes detailed identification keys and taxonomic descriptions. Written by experts in the field and complemented with over 50 color photoplates and maps, Terricolous Lichens in India: Volume 2: Morphotaxonomic Studies is a valuable resource for researchers and students interested in the field of lichenology.
Keywords: Life sciences; Biochemistry; Botany; Plant anatomy; Plant breeding; Plant physiology; Life Sciences; Plant Sciences; Plant Biochemistry; Plant Anatomy/Development.; Plant Physiology; Plant Genetics & Genomics